Slip and Hall Effects on Peristaltic Rheology of Copper-Water Nanomaterial Through Generalized Complaint Walls With Variable Viscosity - Awais, Muhammad; Kumam, Poom; Parveen, Nabeela; Ali, Aamir; Shah, Zahir; Thounthong, Phatiphat (Frontiers in Physics, 2020)
Current research is devoted to investigate the influence of rotation on MHD natural convection peristaltic flow of copper-water nanofluid. Higher-order slip conditions along with flexible channel walls are taken into an account. Viscous dissipation combined with Hall properties, temperature-dependent viscosity, generative/ absorptive and radiative effects have been investigated. Mathematical modeling is performed and the consequential coupled system of differential equations is simplified by adopting lubrication approximation. The simplified differential system is tackled numerically and the results for flow quantities are physically interpreted via graphs in order to describe the impact of assorted parameters